Thermodynamic, rheological and structural properties of edible oils structured with LMOGs: Influence of gelator and oil phase. (April 2018) - Fasolin, L.H.; Cerqueira, M.A.; Pastrana, L.M.; Vicente, A.A.; Cunha, R.L.
Graphical abstract: Highlights: Biocompatible organogels were produced with GRAS compounds. The influence of the compounds depended on the level (molecular, colloidal, macro). Thermodynamic properties exerted influenced on the structure, changing the rheology. Glycerol polar heads were more prone to interact with each other. There were synergistic effects between molecular interactions and spatial arrangement. Abstract: The effect of different oil phases and low molecular weight organogelators (LMOGs) structures on edible oils was investigated through differential scanning calorimetry (DSC), rheology and small-angle X-ray scattering (SAXS). Different gelators (glyceryl tristearate–GT; sorbitan tristearate–ST; sorbitan monostearate–SM and glyceryl monostearate-GM) were tested in medium-chain triglycerides and high oleic sunflower (named MCT and LCT). Systems were thermoreversible and their thermodynamic properties were dependent on the combined effect of the interactions of structurants' polar head with other constituents and the sterical effect of their hydrophobic tails. The crystallization onset temperature was higher for GM and SM, possibly due to the lower sterical effect of their tails. However, the corresponding enthalpy and entropy change values were influenced by the hydrophilic head group: glycerol-based organogelator molecules were able to interact strongly than sorbitans, increasing these values. Rheological studies showed that gels produced with LCT were stronger than with MCT. Moreover, cooling and heating cycles showed more than one transition and shear dependence. Stronger structures were more sensitive to temperature, possibly because of their more organized structure that destabilizes more easily with the increase of molecular mobility. These results were in agreement with the SAXS analyses. At 50 °C, the stronger networks lost their initial structure, and at 70 °C they collapsed. Thus, molecular interactions and structurant self-assembly were dependent on the structurant + solvent combination, leading to different physicochemical properties and thermal stability. It is expected that these results will allow customizing properties of structured oil for diverse applications, spanning from food to cosmetic and pharmaceutical industries.